Impact of anemia on in‐hospital complications after ischemic stroke. (9th March 2018) - Wei, C.‐C.; Zhang, S.‐T.; Tan, G.; Zhang, S.‐H.; Liu, M.
Abstract : Background and purpose: In‐hospital complications after stroke represent barriers to optimal recovery and are even potentially life‐threatening. Anemia is common in stroke patients and is related to poor outcome after stroke. Less is known, however, of the association of anemia with complications. We aimed to investigate the impact of anemia on a series of in‐hospital complications after ischemic stroke. Methods: Consecutive patients with ischemic stroke within 7 days were included. Anemia on admission and its severity were defined according to World Health Organization criteria. Eight pre‐specified complications, such as pneumonia, gastrointestinal bleeding (GIB) and hemorrhagic transformation, were recorded during hospitalization. Results: A total of 2647 patients were included. Anemia was present in 648 patients (24.5%), and 883 patients (33.4%) experienced at least one complication. Patients with anemia were more likely to experience one or more complications, pneumonia, GIB and thromboembolism (all P < 0.001) than patients without anemia. After adjustment for the confounders, patients with anemia had an adjusted odds ratio for at least one complication of 1.539 [95% confidence interval (CI), 1.232–1.923], for pneumonia of 1.707 (95% CI, 1.345–2.167), for GIB of 2.245 (95% CI, 1.215–4.148) and for thromboembolism of 3.443 (95% CI, 1.668–7.108). The risk of at least one complication, pneumonia, GIB and thromboembolism increased with anemia severity (all P < 0.05). There was no significant association between anemia and urinary tract infection, hemorrhagic transformation, seizures and brain herniation. Conclusion: Anemia is an independent predictor of in‐hospital complications following stroke, especially for pneumonia, GIB and thromboembolism. It remains to be studied whether prophylaxis and treatment of anemia would prevent in‐hospital complications.